Monocytes from Irf5(−/−) mice have an intrinsic defect in their response to pristane-induced lupus - Yang, Lisong (2012)
The transcription factor interferon regulatory factor 5 (IRF5) has been identified as a human systemic lupus erythematosus (SLE) susceptibility gene by numerous joint linkage and genome-wide association studies. Although IRF5 expression is significantly elevated in primary blood cells of SLE patients, it is not yet known how IRF5 contributes to SLE pathogenesis. Recent data from mouse models of lupus indicate a critical role for IRF5 in the production of pathogenic autoantibodies and the expression of Th2 cytokines and type I IFN. In the current study, we examined the mechanism(s) by which loss of Irf5 protects mice from pristane-induced lupus at early time points of disease development. We demonstrate that Irf5 is required for Ly6C(hi) monocyte trafficking to the peritoneal cavity (PC), which is believed to be one of the initial key events leading to lupus pathogenesis in this model. Chemotaxis assays using peritoneal lavage from pristane-injected Irf5(+/+) and Irf5(−/−) littermates support an intrinsic defect in Irf5(−/−) monocytes. We found the expression of chemokine receptors CXCR4 and CCR2 to be dysregulated on Irf5(−/−) monocytes and less responsive to their respective ligands, CXCL12 and CCL2. Bone marrow reconstitution experiments further supported an intrinsic defect in Irf5(−/−) monocytes since Irf5(+/+) monocytes were preferentially recruited to the PC in response to pristane. Together, these findings demonstrate an intrinsic role for IRF5 in the response of monocytes to pristane, and their recruitment to the primary site of inflammation that is thought to trigger lupus onset in this experimental model of SLE.